Dimensionamento ótimo de painéis fotovoltaicos usando enxame de partículas modificado para reduzir as perdas de energia e melhorar o perfil de tensão. - Souza, Jeane Silva de (2016)
This work presents a method of sizing photovoltaic panels using modified Particle swarm (MPSO) in order to reduce power losses and improve the voltage profile. For implementation was used the PowerFactory® software, specifically programing language DIgSILENT (DPL). The proposed method was applied at the first time in the IEEE 13-bus system. After validating, it was applied to a real system, Federal University of Paraíba (UFPB). The results show that the proposed method have the ability to provide the best dimensions of photovoltaic panels distributed at the University, improving of the voltage profile and reducing energy losses